1995
DOI: 10.1007/bf00032007
|View full text |Cite
|
Sign up to set email alerts
|

UV-B-tolerance of alpine and arctic Daphnia

Abstract: Survival of transparent and pigmented Daphnia from alpine as well as arctic habitats, exposed to solar radiation with total or reduced UV-B, was measured . In the alpine pond, survivorship and reproduction of transparent juvenile as well as adult Daphnia were significantly reduced due to LTV-B . Transparent adult arctic Daphnia also showed significant reduction in survivorship when exposed to total, when compared with controlled solar radiation . In contrast, heavily melanized adult arctic Daphnia showed no in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 9 publications
1
14
0
Order By: Relevance
“…Our results suggested some variability in susceptibility between pigmented populations, but failed to show any strong effect of post-irradiation light repair, in contrast to the findings of Siebeck & Bohm (1994). The laboratory experiments demonstrated the lower UV-B susceptibility of melanized Daphnia, supporting the findings of Hebert & Emery (1990), Zellmer (1995) and Hessen (1996), and the prediction that heavily melanized individuals in the shallowest locality are most tolerant to UV (Fig. 3).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Our results suggested some variability in susceptibility between pigmented populations, but failed to show any strong effect of post-irradiation light repair, in contrast to the findings of Siebeck & Bohm (1994). The laboratory experiments demonstrated the lower UV-B susceptibility of melanized Daphnia, supporting the findings of Hebert & Emery (1990), Zellmer (1995) and Hessen (1996), and the prediction that heavily melanized individuals in the shallowest locality are most tolerant to UV (Fig. 3).…”
Section: Discussionsupporting
confidence: 86%
“…comprise a species complex with astonishing clonal complexity and genetic variability (Weider, Beaton et al 1987;Hobzk & Wolf 1991;Colboume et al 1998). Most remarkable is the co-existence of morphotypes with and without carapace melanization (Hebert & Emery 1990;Zellmer 1995;Hessen 1996). Highly light-exposed Daphnia populations Table 1.…”
Section: Introductionmentioning
confidence: 99%
“…1). This could be due to the more severe UVR effects on dividing cells in the offspring (Zellmer 1995) or a generally more explorative behavior of older individuals. The refuge demand, that is, the overall escape behavior, was highly repeatable within individuals when analyzing mothers and daughters together (Table 1), suggesting individual consistency, that is, that some individuals are more risk taking than others over consecutive exposures.…”
Section: Discussionmentioning
confidence: 99%
“…wavelengths >295 nm) the potential DNA damage increases exponentially with decreasing wavelength. Many studies have shown reduced survival in different zooplankton species after UVR exposure (19)(20)(21). However, the response to UVR shows enormous variability among species (20,(22)(23)(24)(25)(26), life stages (21,27), pigmented morphs (compared with nonpigmented morphs) (28) and even within single species (24,29,30).…”
Section: Uvr Effects On Zooplankton and Counteracting Strategiesmentioning
confidence: 99%